Long-term projections of supply and demand for agricultural products in Israel - Mundlak, Yair.; Halevi, Nadav; Falk Project for Economic Research in Israel (Jerusalem : Faculty of Agriculture, Hebrew University, 1964)
This volume summarizes and analyzes the results of a study of the supply and demand for agricultural products in Israel for the years 1965 and 1975.
Report prepared for the Economic Research Service and the Foreign Agricultural Service of the U.S. Dept. of Agriculture, under contract with the Falk Project for Economic Research in Israel, by the Dept. of Agricultural Economics of the Hebrew University, Jerusalem.
Includes bibliographical references and index.
ne 25/01/2019
Loans
Keywords: Produce trade